Prescribing trends of gabapentin, pregabalin and oxycodone; a secondary analysis of primary care prescribing patterns in England - Green,K; Cooke,O'Dowd N; Watt,H; Majeed,A; Pinder,R (BJGP Open, 2019)
BackgroundThe risk of iatrogenic harm from prescription drug use, misuse and abuse of drugssuch as gabapentin, pregabalin and oxycodone is substantial. In recent years, deathsassociated with these drugs in England have increased.AimsTo characterise general practice prescribing trends for gabapentin, pregabalin andoxycodone – termed dependence forming medicines (DFM) – in England and describepotential drivers of unwarranted variation.Design and SettingThis study is a retrospective secondary analysis of open source, publicly availablegovernment data from various sources pertaining to primary care demographics andprescriptions.MethodsThis study used five consecutive years (April 2013 – March 2018) of aggregate datato investigate longitudinal trends of prescribing and variation in prescribing trends atpractice and clinical commissioning group (CCG) level.ResultsAnnual prescriptions of gabapentin, pregabalin and oxycodone have increased eachyear over the period. Variation in prescribing trends were associated with GP practicedeprivation quintile, where the most deprived GP practices prescribe 313% (p<0.001)and 238% (p<0.001) greater volumes of gabapentin and pregabalin per person thanpractices in the least deprived quintile. The highest prescribing CCGs of each of thesedrugs were predominantly in northern and eastern regions of England.ConclusionsSubstantial increases in gabapentin, pregabalin and oxycodone prescriptions areconcerning and will increase iatrogenic harm from drug-related morbidity and mortality.More research is needed to understand the large variation in prescribing between general practices; and to develop and implement interventions to reduce unwarrantedvariation and increase the appropriateness of prescribing of these drugs.